Using critical flame temperature for estimating lower flammable limits of a mixture. Issue 4 (4th May 2013) - Ma, Tingguang
<x xml:space="preserve">Abstract</x> Based on the thermal balance between quenching and heating potentials of each component (fuel/oxygen/diluent), a method of computing flame temperature is proposed. This method can be used to find the critical flame temperature at lower flammable limits or estimate the lower flammable limits with an assumed critical flame temperature. © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 387–392, 2013